Empowerment of Disabilities Through Creative Dance Activities as a Step to Support the Healthy Living Community Movement Towards a Fit Indonesia 2045 - Wijayanti, Dwi Gansar Santi; Setiawan, Ipang; Irsyada, Roas; Farida, Lulu April; Husna, Aftina Nurul; Indriyani, Silvia; Sahab, Dhoni Frizky Arya; Tadita, Armayta Dwi; Suminar, Suminar (Universitas Negeri Semarang, 2025)
People with disabilities, especially students at SLB Negeri Ungaran, have the same right to live a healthy and active life as other individuals. One way to achieve this is through physical activity such as Creative Dance. Creative Dance has many benefits for people with disabilities, both physically, psychologically, and socially. Physically, it helps to improve physical fitness. Psychologically, it increases confidence, reduces stress, and helps overcome anxiety and depression. Meanwhile, in the social aspect, it provides opportunities for people with disabilities to interact with others, build social relationships, and increase a sense of togetherness and inclusion in society. Participation in group activities can also increase motivation as well as provide positive emotional support. The purpose of this community service activity is to increase the independence, motor skills, and confidence of people with disabilities through physical activities based on creative dance. The implementation methods in this activity are (1) socialization, (2) training, and (3) mentoring. This activity was attended by 151 students with disabilities. During the implementation of the service, the participants showed enthusiasm, this can be seen from the attendance of 90% of the participants and active involvement in the creative Dance session. The result of this service activity is to have a positive impact, both physically, psychologically, and socially, on the participants. Creative Creative Dance has proven to be an effective medium to improve the fitness, creativity, social interaction, and confidence of people with disabilities.